2009
DOI: 10.1111/j.1538-7836.2009.03434.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential stimulation of monocytic cells results in distinct populations of microparticles

Abstract: Summary Background Microparticles (MPs), small vesicles shed from stimulated cells, permit cross-talk between cells within a particular environment. Their composition is thought to reflect their cell of origin, and differs according to whether they are produced by stimulation or by apoptosis. Whether MP properties vary according to stimulus is not yet known. Methods We studied the characteristics of MPs produced from monocytic THP-1 cells upon stimulation with lipopolysaccharide or a soluble P-selectin chim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
114
3
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(136 citation statements)
references
References 39 publications
12
114
3
7
Order By: Relevance
“…However, whether the elevated level of SD MVs with selectively enriched proteins is induced via these mechanisms has yet to be studied. Although it was reported that stimulation of cells did not result in changes in the size distribution of MVs [9] , we observed that SD resulted in a different size distribution of MVs compared with non-SD conditions. We found that MVs with diameters below 0.5 μm significantly increased in number after SD treatment, whereas MVs larger than 0.5 μm decreased in number.…”
Section: Discussioncontrasting
confidence: 49%
See 4 more Smart Citations
“…However, whether the elevated level of SD MVs with selectively enriched proteins is induced via these mechanisms has yet to be studied. Although it was reported that stimulation of cells did not result in changes in the size distribution of MVs [9] , we observed that SD resulted in a different size distribution of MVs compared with non-SD conditions. We found that MVs with diameters below 0.5 μm significantly increased in number after SD treatment, whereas MVs larger than 0.5 μm decreased in number.…”
Section: Discussioncontrasting
confidence: 49%
“…Upon cleavage by cytosolic esterases, calcein binds to calcium, becomes fluorescent, and is retained within MVs. Thus, only intact MVs will fluoresce, and concomitant staining of debris is avoided [9] . The data suggested that our MV sample collected following the differential centrifugation protocol had a purity of 70% ( Figure 2F), and cell debris or mass-molecule compounds were observed as calcein-negative events in the FACS analysis.…”
Section: Validation Of Mvsmentioning
confidence: 99%
See 3 more Smart Citations